1998
DOI: 10.1002/(sici)1097-0185(199808)251:4<528::aid-ar9>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Origin, course, and laterality of spinocerebellar axons in the North American Opossum,Didelphis virginiana

Abstract: Spinocerebellar axons have been studied extensively in placental mammals, but there have been no full reports on their origin, laterality, or spinal course in any marsupial. We have used the North American opossum (Didelphis virginiana) to obtain such information and to ask whether any spinocerebellar neurons innervate both the anterior and posterior lobes of the cerebellum through axonal collaterals. To identify spinal neurons that project to the cerebellum, we employed the retrograde transport of Fluoro-Gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…There are no previous reports of pTDP-43 pathology in neurons of Clarke’s column, although mild neuronal loss in the posterior thoracic nucleus has been noted in cases with a long duration of disease [26]. Clarke’s column neurons receive proprioceptive afferences from skeletal muscles and project to the cerebellum via the posterior spinocerebellar tract [57]. However, all neurons of lamina VII are also targeted by brain regions involved in motor functioning, including the motor cortex, red nucleus, and periaqueductal gray matter [14, 61].…”
Section: Discussionmentioning
confidence: 99%
“…There are no previous reports of pTDP-43 pathology in neurons of Clarke’s column, although mild neuronal loss in the posterior thoracic nucleus has been noted in cases with a long duration of disease [26]. Clarke’s column neurons receive proprioceptive afferences from skeletal muscles and project to the cerebellum via the posterior spinocerebellar tract [57]. However, all neurons of lamina VII are also targeted by brain regions involved in motor functioning, including the motor cortex, red nucleus, and periaqueductal gray matter [14, 61].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively fewer degenerative changes in the cervical spinal cord can be partially explained by a ''dilutional effect'' of unaffected ascending fibers from thoracic limbs, cervical musculature, and other cranial structures and of unaffected proximal descending fibers from upper motor neuron centers. 27,30,31,35 The predominance of lesions in the thoracic spinal cord, however, cannot be fully explained by normal anatomic changes in tract sizes at different segmental levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the motor field, corollary discharge is a mechanism by which copies of descending motor signals are sent back to the proprioceptive sensory pathways to distinguish self-generated movements from externally generated ones (Sperry, 1950; von Holst and Mittelstaedt, 1950; Crapse and Sommer, 2008). In mammals, to the best of our knowledge, there has been no evidence of corollary discharge occurring at the level of MNs themselves, although retrograde labeling studies of spinocerebellar neurons have reported cerebellar-projecting neurons whose cell bodies reside in the MN lamina IX of the spinal cord (Matsushita and Hosoya, 1979; Matsushita et al, 1979; Terman et al, 1998). In addition, Cooper and Sherrington in their initial description of ascending projections from the spinal cord observed “large cells” in the ventral horn that degenerated upon cutting their ascending axons (Cooper and Sherrington, 1940).…”
Section: Introductionmentioning
confidence: 99%